2004
DOI: 10.1007/s11060-004-9170-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study for O6-methylguanine-DNA methyltransferase in the non-neoplastic and neoplastic components of gliomas

Abstract: Although the expression O6-methylguanine-DNA methyltransferase (MGMT) is an important hallmark for decision of nitrosourea chemotherapy for glioma patients, no immunohistochemical method for analysis of MGMT has been standardized yet. Gliomas usually contain non-neoplastic cells even deep in the tumor. It is not known which of these components expresses MGMT. To clarify this point, we investigated MGMT expression in the non-neoplastic cells in autopsy and surgical specimens by immunohistochemistry. High grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 17 publications
7
62
0
Order By: Relevance
“…MIB-LI ( 5%/>5%) and tumour grade (grades II/IV). The cut-off value so determined was 10.50%, which was similar to Nakasu et al 27 However it is suggested that a larger population size with proper follow-up data be studied, in order to ensure a better correlation of this value.…”
Section: Discussionsupporting
confidence: 73%
“…MIB-LI ( 5%/>5%) and tumour grade (grades II/IV). The cut-off value so determined was 10.50%, which was similar to Nakasu et al 27 However it is suggested that a larger population size with proper follow-up data be studied, in order to ensure a better correlation of this value.…”
Section: Discussionsupporting
confidence: 73%
“…Nakasu et al analyzing neoplastic and non-neoplastic cells of gliomas, found that tumors always presented an MGMT-positive normal cell component. Considering a cut-off point at 10% of the normal cell component in glioma samples for discriminating the negative tumor from the positive one, they showed that MGMT negative expression tumor was a significant factor for survival (P<0.05) in the patient treated with ACNU (20).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the first question, it is important to note that MGMT expression was reported to be present in non-neoplastic endothelial cells, astrocytes, oligodendroglial cells, and in inflammatory cells within a glioma. 23 Furthermore, it has been demonstrated that MGMT expression can be induced by glucocorticoids, ionizing radiation, and genotoxic agents, including those used during chemotherapy. [24][25][26] Determination of the hypermethylation status of the MGMT promoter therefore remains warranted, as it provides information on the ability of the tumor cells to express AGT independent of their expression levels before chemotherapy.…”
Section: Immunohistochemical Detection Of Mgmt Expressionmentioning
confidence: 99%